Considerations and methods for placebo controls in surgical trials (ASPIRE guidelines). Issue 10226 (7th March 2020) - Beard, David J; Campbell, Marion K; Blazeby, Jane M; Carr, Andrew J; Weijer, Charles; Cuthbertson, Brian H; Buchbinder, Rachelle; Pinkney, Thomas; Bishop, Felicity L; Pugh, Jonathan; Cousins, Sian; Harris, Ian A; et al.
Summary: Placebo comparisons are increasingly being considered for randomised trials assessing the efficacy of surgical interventions. The aim of this Review is to provide a summary of knowledge on placebo controls in surgical trials. A placebo control is a complex type of comparison group in the surgical setting and, although powerful, presents many challenges. This Review outlines what a placebo control entails and present understanding of this tool in the context of surgery. We consider when placebo controls in surgery are acceptable (and when they are desirable) in terms of ethical arguments and regulatory requirements, how a placebo control should be designed, how to identify and mitigate risk for participants in these trials, and how such trials should be done and interpreted. Use of placebo controls is justified in randomised controlled trials of surgical interventions provided there is a strong scientific and ethical rationale. Surgical placebos might be most appropriate when there is poor evidence for the efficacy of the procedure and a justified concern that results of a trial would be associated with high risk of bias, particularly because of the placebo effect. Feasibility work is recommended to optimise the design and implementation of randomised controlled trials. This Review forms an outline for best practice and provides guidance, in the form of the Applying Surgical Placebo in Randomised Evaluations (known as ASPIRE) checklist, for those considering the use of a placebo control in a surgical randomised controlled trial.